The Rationale Behind the Influence of English on Modern Colloquial Sinhala Language - Gamage, Upul Priyantha; Dilani, Nipunika (Advances in Social Sciences Research Journal, 2022)
The causes of language influence that come under contact linguistics is a topic of common interest among linguistic academics nowadays. Sinhala is the majority language in Sri Lanka that has evolved over 2000 years and during this long retro, it has had both oriental and occidental language influences while the major impact has received from western languages after colonising the country. This piece of research employed two primary data collection methods: participatory observation and chunk recordings while collecting secondary data from the previous literature. As the sampling strategy, we used convenient sampling and the analytical technique of data was content analysis. The main objective of conducting this research was to find out the exact causes of the English language influence on modern colloquial Sinhala over the last 200 years. The study has established the main causes of English language influence on modern colloquial Sinhala as linguistic and cultural hegemony, colonisation, American expansion, superiority of social class, globalisation, commercial, industrial and religious factors while language contact is recognised as an umbrella term for these root causes. In conclusion, there have been two broad directions of these causes of English language influence that had taken place. At the beginning of the colonial rule, it had become top-bottom and now it has transferred to bottom-up, and the influence of English in the modern period on Sinhala has become complementary and multidimensional while the political influence behind the process in its nature is soft and arbitrary.